Lente metamaterial para constru????o de uma antena de alto ganho em microondas - Ribeiro, D??bora Costanti Justino (2020)
This work presents the development of a metamaterial lens built in a printed circuit laminate suitable for the microwave range. For the design and analysis, a theoretical study of the metamaterial was carried out, with this medium consisting of insertions of metallic pins and resonant rings in an isotropic dielectric substrate. As the study of lenses requires the description of the medium refractive index, this characteristic was analyzed in the metamaterial, including the frequency effects. The development of the flat lens was based on the spherical model of L??neburg. A similar behavior of the metamaterial was achieved using metallic films in the shape of I and H, with dimensions varying radially from the center of the structure. To determine these dimensions, for which there is no closed analytical treatment, computer simulations were performed, using the programs Comsol Multiphysics??? and Matlab??? . A prototype of the lens was developed and measurements were made with the equipment in the semi-anechoic chamber of the National Telecommunications Institute. The excitation of the lens was through a monopole antenna perpendicular to the plane of the lens. Without the lens acting, there is an omnidirectional emission in the plane perpendicular to the axis of the monopole. In this way, its influence on the radiation diagram became more evident. The tests proved a marked change, so that the association of the monopole and the lens guaranteed an increase of more than 20dB in the field intensity emitted in the maximum radiation direction.